The relationship between knowledge and the compliance level of PBPU participants in paying JKN contribution in Tumpang - Pungky Firdausi; Dewiyani, AAI Citra (BKM Public Health and Community Medicine, 2021)
JKN is a programme in the form of health protection so that participants can get the benefits of health care and protection provided to everyone who has paid contributions or whose contributions have been paid by the government. The increasing number of PBPU participants isn’t followed with level of compliance in paying contribution. One of the causes of deficit in BPJS Kesehatan is the level of compliance of PBPU participants in Indonesia in paying contribution only reached 59%. Objective: This study aimed to determine the relationship between knowledge and the compliance level of PBPU Participants in Paying JKN Contribution in Tumpang. Method: Research design of this study is quantitative analytic study with cross sectional approach. The sampling technique used simple random sampling method on 100 samples with the following criteria: JKN PBPU participants in Tumpang, aged 15 - 64 years, and willing to become respondents. Results: As much as 70% of the total respondents have good knowledge and 30% respondents have less knowledge. Meanwhile the level of compliance is 55% obeyed the JKN contribution and 45% did not comply with the JKN contribution. Conclusions: The results of statistical tests using Chi-Square showed that the P-Value = 0.000 which is smaller than α = 0.05. So that statistically there is a relationship between knowledge and the compliance level of PBPU Participants in Paying JKN Contribution in Tumpang. BPJS Kesehatan is expected to increase socialization related to the JKN program and for further researchers it is recommended to add other variables that will affect the compliance level of PBPU Participants in Paying JKN Contribution.